2022
DOI: 10.3390/pharmaceutics14061215
|View full text |Cite
|
Sign up to set email alerts
|

Nanospermidine in Combination with Nanofenretinide Induces Cell Death in Neuroblastoma Cell Lines

Abstract: A new strategy to cause cell death in tumors might be the increase of intracellular polyamines at concentrations above their physiological values to trigger the production of oxidation metabolites at levels exceeding cell tolerance. To test this hypothesis, we prepared nanospermidine as a carrier for spermidine penetration into the cells, able to escape the polyamine transport system that strictly regulates intracellular polyamine levels. Nanospermidine was prepared by spermidine encapsulation in nanomicelles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…We have also observed that forced expression of SMOX promotes cell cycle arrest and apoptosis of FN-RMS cells, with a concomitant reduction of their tumorigenic features, such as anchorage-independent growth. These results are in agreement with the previous finding that an increase in SPD intracellular levels induces reactive oxygen species (ROS) production (i.e., H 2 O 2 ), this leading to the death of neuroblastoma, breast or lung cancer cells ( McCloskey et al, 1996 ; Pledgie et al, 2005 ; Lodeserto et al, 2022 ). In this regard, it has to be considered an increase in SPD intracellular levels can cause cancer cell death also in a ROS-independent manner through Bim activation ( Guo et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We have also observed that forced expression of SMOX promotes cell cycle arrest and apoptosis of FN-RMS cells, with a concomitant reduction of their tumorigenic features, such as anchorage-independent growth. These results are in agreement with the previous finding that an increase in SPD intracellular levels induces reactive oxygen species (ROS) production (i.e., H 2 O 2 ), this leading to the death of neuroblastoma, breast or lung cancer cells ( McCloskey et al, 1996 ; Pledgie et al, 2005 ; Lodeserto et al, 2022 ). In this regard, it has to be considered an increase in SPD intracellular levels can cause cancer cell death also in a ROS-independent manner through Bim activation ( Guo et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless however, search for efficient and selective SMOX or PAOX inhibitors of is still ongoing ( Di Paolo et al, 2019 ). Recently, nanoSPD have been used to carry SPM into neuroblastoma cells, impairing cell growth and potentiating the effects of nanofenretidine in vitro ( Lodeserto et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The dry product was reconstituted with water to 50 mg/mL NF and stored at −22 °C until use. Spermidine nanomicelles were prepared as previously reported [ 22 ] by mixing soy phosphatidylcholine (4 mmoles), glyceryl tributyrate (2 mmoles), 2-hydroxypropyl beta cyclodextrin (0.4 mmoles), KOH 10 N (400 µL, 4 mmoles), and spermidine (2 mmoles) to homogeneity to obtain a semisolid phase that was dispersed in PBS pH 7.4 to 50 mg/mL. The coarse nanomicelle suspension obtained was filtered through 0.2 µm filters, dialyzed for 72 h (dialysis membrane Mw cutoff 10 KD) against PBS pH 7.4, and then, the dialyzed phase was lyophilized.…”
Section: Methodsmentioning
confidence: 99%
“…Nanofenretinide is a nanoformulation based on phospholipid nanomicelles containing fenretinide, which demonstrated activity in a wide range of tumor cell lines and xenograft models [ 18 , 19 , 20 , 21 , 22 ]. The ability of Nanofenretinide to penetrate tumor cells and transport high drug amounts has been proven in NB cells that showed higher intracellular drug concentrations with respect to free fenretinide [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation